Enhancing adolescents' motivation for science : research-based strategies for teaching male and female students - Shumow, Lee; Schmidt, Jennifer A.; American Psychological Association. Division of Educational Psychology (Thousand Oaks, California : Corwin, a Sage company, 2014)
Draws upon the Science-in-the-Moment (SciMo) Project to offer strategies, consistent with Next Generation Science Standards, to motivate high school students and foster scientific literacy.
Introduction: motivation to learn science -- Value -- Affiliation -- Autonomy -- Confidence -- Success -- Goal orientation -- Ability beliefs -- Challenge -- Emotion.
A joint publication of Division 15 (Educational Psychology) of the American Psychological Association.
Includes bibliographical references (pages 147-163) and index.
Keywords: Science -- Study and teaching (Secondary); Motivation in education; Sex differences in education; Motivation in education; Science -- Study and teaching (Secondary); Sex differences in education